2014
DOI: 10.1021/ja407911b
|View full text |Cite
|
Sign up to set email alerts
|

Photoemission Mechanism of Water-Soluble Silver Nanoclusters: Ligand-to-Metal–Metal Charge Transfer vs Strong Coupling between Surface Plasmon and Emitters

Abstract: Using carboxylate-protected silver nanoclusters (Ag-carboxylate NCs) as a model, we separately investigated the contribution of the ligand shell and the metal core to understand the nature of photoluminescence of Ag NCs. A new Ag(0)NCs@Ag(I)-carboxylate complex core-shell structural model has been proposed. The emission from the Ag-carboxylate NCs could be attributed to ligand-to-metal-metal charge transfer from Ag(I)-carboxylate complexes (the oxygen atom in the carboxylate ligands to the Ag(I) ions) to the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
192
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(202 citation statements)
references
References 32 publications
6
192
0
Order By: Relevance
“…It is assumed that charge transfer states provided by electron rich ligands are responsible for the effective enhance luminescence in clusters, as for example it is assumed to occur in large thiolate protected gold clusters (Au > 18) involving -RS-Au-RS-Au-RS staple motifs [18,19]. Therefore, the presence of large Stokes shifts observed in clusters has been interpreted assuming a similar mechanism based on ligand-to-metal charge transfer (LMCT) absorptions involving electron-rich atoms or groups attached to the cluster core [20][21][22]. But, a definitive evidence for this mechanism is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that charge transfer states provided by electron rich ligands are responsible for the effective enhance luminescence in clusters, as for example it is assumed to occur in large thiolate protected gold clusters (Au > 18) involving -RS-Au-RS-Au-RS staple motifs [18,19]. Therefore, the presence of large Stokes shifts observed in clusters has been interpreted assuming a similar mechanism based on ligand-to-metal charge transfer (LMCT) absorptions involving electron-rich atoms or groups attached to the cluster core [20][21][22]. But, a definitive evidence for this mechanism is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…3c and 3d, the molar fraction of Pt 0 in total Pt species is 82.3% for Au 2 Pt 1 , which is higher than that of Au 1 Pt 1 (73.3%). It has been widely reported that a certain proportion of incompletely reduced precursors exists in Pt, Au or Ag nanoparticles, since strong coordination of metal cations with electron-rich groups of organic templates hinders the reduction process (Chen et al 2014a;Desireddy et al 2013;Knecht et al 2008;Wei et al 2010). Therefore, it can be deduced that Au + -coordination with nucleobases decreases the proportion of DNA-bound Pt 2+ .…”
Section: Physicochemical Properties Of Dna-stabilized Nanoparticlesmentioning
confidence: 99%
“…[6][7][8] Although silver nanoclusters have similar advantages to AuNCs, their fluorescence is sensitive to the concentration of chloride anions because of strong complexation between Ag (I) and chloride anions. 9 In addition, silver-based nanomaterials are susceptible to oxidizing agents. 10 Numerous innovative synthesis methods have been developed for preparing different-sized AuNCs with fluorescent emissions from the UV to the near IR regions.…”
Section: Introductionmentioning
confidence: 99%